MANSION BATHS OF CYPRUS - Enes Kavalçalan (Zeitschrift für die Welt der Türken, 2015)
From the very beginning of the human history, body cleanliness is one of the basic needs. At first, human beings have supplied the needs of cleaning from rivers and lakes. With the development of civilizations they have started to build baths. In Roman Period these baths have been combined with Gymnasiums and become a part of the social life while they were merely small places of bathing in Ancient Greek. In the course of time, bath architecture which gained new functions and typologies with the effects of different nations and geographic places has maintained its own existence in Turkish culture as a popular ingredient in it. In this paper, mansion baths that were built in Ottoman period in Cyprus are studied. Firstly all locations of baths were determinated, photographed and measured during the research. Then, the determinated baths have been tried to being described comprehensively in the light of the documents and knowledges that are achievable. Main plan in mansion baths was built on the basis of “dressing” and “hotness” sections. Also, there are installation parts like “water tank” and “boiler room”. The baths which have a peculiar schema in itself constitute the exceptional examples of bath typology. With this paper, introduction to science world of mansion baths which are generally ignored in most of the researches because of the small sizes, are aimed.